2016
DOI: 10.1002/bem.22018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of BMP9 and pulsed electromagnetic fields on the proliferation and osteogenic differentiation of human periodontal ligament stem cells

Abstract: Periodontal ligament stem cells (PDLSCs) have been confirmed to have self-renewal capacity and multidifferentiation potential and are good candidates for periodontal tissue regeneration. Pulsed electromagnetic field (PEMF) has been demonstrated to promote osteogenesis in non-union fractures, partly by regulating mesenchymal stem cells or osteoblast activity. However, there is no report about the osteo-inductive effect of PEMF stimulation on human PDLSCs (hPDLSCs). Thus, we tested the hypothesis that PEMF bioph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…hBM-MSC differentiation towards the osteoblastic lineage may be alternately mediated and promoted by different stimuli such as BMP-2 [ 15 ] and BMP-9 [ 16 ] or by the roughness of the growing surface [ 17 ]or by application of external forces [ 9 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…hBM-MSC differentiation towards the osteoblastic lineage may be alternately mediated and promoted by different stimuli such as BMP-2 [ 15 ] and BMP-9 [ 16 ] or by the roughness of the growing surface [ 17 ]or by application of external forces [ 9 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wang and colleagues were able to enhance the osteogenic potential of PLDSCs by transfecting them with BMP9. Moreover, the combination of BMP9 transfection and pulsed electromagnetic field treatment improved the osteogenesis of these cells depicted by an enhanced expression of RUNX2, ALP, and OPN [293]. Ye and colleagues reported that the effect of BMP9 on osteogenesis is mediated through the activation of the MAPK signaling pathway via the phosphorylation of p38 and ERK1/2.…”
Section: Regulation Of Growth Factors In Osteogenesis In Periodontal Ligament Stem Cellsmentioning
confidence: 98%
“…Similarly, PEMF stimulation of periodontal ligament stem cells increased the osteogenic potential of the cells ( Wang et al, 2017 ). Moreover, prolonged exposure to PEMF of MSCs isolated from the human umbilical cord was found to enhance the tenogenic potential ( Marmotti et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%